CONTROL AND GUIDANCE SYSTEM FOR HYBRID UNDERWATER GLIDER USING GAIN SCHEDULED PID CONTROLLER AND LINE-OFSIGHT ALGORITHM - Putri Priandiri, Vidya
Autonomous Underwater Vehicles (AUVs) have become increasingly important in such military and scientific sectors. Having advantages in its maneuverability and agility makes AUV consumes much energy. In the meantime, AUV has a subclass of same underwater vehicle known as Autonomous Underwater Glider (AUG) which glides up and down underwater, so it consumes not so much energy. Combining both AUV and AUG is an innovation in recent years for building Hybrid Underwater Glider (HUG) so the vehicle can be agile yet consumes less energy. The dynamic model of HUG is highly nonlinear so designing the control system and guidance system for this vehicle would be difficult and become complex. The control system is responsible to generate the (desired) position and attitude of HUG as vehicle movement. In this research, the PID controller will be employed to control the nonlinear HUG hence there are several parameters that being neglected due to using the one of classical control theories that control the linear system. However, the PID controller would be scheduled by surge speed of the vehicle in order to approach the nonlinear parameter that being neglected. Then, to overcome the overshoot issue that may be happened, the gain scheduled PID controller is added up with anti-windup bumpless transfer scheme. The HUG is equipped with a guidance system to ease the vehicle reach the given waypoint from user. Guidance system is responsible to determine the heading of the vehicle. In this research, the guidance system utilizes Line-of-Sight method to measure the distance between waypoint and vehicle. The simulation of this control and guidance system for HUG is conducted through Hardware in the Loop Simulation (HILS). The result of control system shows that every subcontrol system has overshoot by 0%-5% and yield 0% of steady sate error for SILS scenario but for HILS scenario, every sub-control system has steady state error by 0%-4% and yield overshoot by 5%-50%. Meanwhile, the result of guidance system shows that Line-of-Sight algorithm is already implemented through SILS and HILS and effectively ease the vehicle to reach the given waypoint and set the heading for vehicle.